TINJAUAN LITERATUR: POLA NORMALIZATION BEHAVIOR PADA ORANGTUA YANG HIDUP DENGAN ANAK SAKIT KRONIS - Hendrawati, Sri; Nurhidayah, Ikeu; Sutini, Tititn (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Chronic illness in children has an impact, whether physical, psychological, social, spiritual, cultural or economic, not only for themselves but also for their parents and families. Parents have a significant role in helping children with chronic illnesses adapt to the illness and achieve optimal growth. Normalization is a process whereby families try to normalize their daily lives while having children with chronic illnesses. This literature review aims to identify normalization behaviour in parents living with chronically ill children. Articles were collected through EBSCOhost, PubMed, Science Direct, and Scopus electronic database using the keywords normalization behaviour, parent, and chronically ill children using qualitative and quantitative studies. The reviewed articles were only articles with full text, written in English, and published from 2015 to 2024. The methodological quality of this literature review was assessed according to the guidelines of the Critical Appraisal Skills Programme. It found 54 articles and only seven articles met the criteria. In families, especially parents who are experiencing difficulty in coping with chronic illness, there were recommended to promote normalization. Normalization behaviour consists of acknowledging that the impairment is present, defining life as usual, minimizing the social consequences of the illness, and engaging in behaviour that demonstrates normalcy to others. In addition, an individual or family who normalizes accepts that there is a deviation from health but strives to live as usually as possible despite the limitations. Nurses can assist the family in performing normalization behaviour by reviewing the family's daily routines, providing social support, enhancing coping strategies, enhancing family closeness, and identifying family or community support sources